2012
DOI: 10.1080/10538720.2012.669369
|View full text |Cite
|
Sign up to set email alerts
|

“I’m Part of This Family”: How Five Care-Giving Partners of Gay Men Story Their Experiences

Abstract: First, my family: thank you Miami (not the city!), Mamali, and Paparesh in particular for the unconditional love you have provided me with, not only at this admittedly uncertain period of time, but also at every possible moment spanning the entirety my life. Baba'ee, I dedicate this project to you. Thank you to my extended family for the many warm wishes sent my way during my time as a graduate student. Thank you also to Sarah Taylor, whose unparalleled kindness, generosity, and sense of humour have undoubtedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…In addition to instrumental care (e.g., transportation, grocery shopping, laundry), LGBT caregivers provide social and emotional support to their friends and partners (Cantor, Brennan, & Shippy, 2004; Muraco & Fredriksen-Goldsen, 2011). In turn, providing assistance to friends and partners provides many LGBT caregivers with positive gains such as an elevated sense of self-esteem and self-efficacy (Kia, 2012; Muraco & Fredriksen-Goldsen, 2011). …”
mentioning
confidence: 99%
“…In addition to instrumental care (e.g., transportation, grocery shopping, laundry), LGBT caregivers provide social and emotional support to their friends and partners (Cantor, Brennan, & Shippy, 2004; Muraco & Fredriksen-Goldsen, 2011). In turn, providing assistance to friends and partners provides many LGBT caregivers with positive gains such as an elevated sense of self-esteem and self-efficacy (Kia, 2012; Muraco & Fredriksen-Goldsen, 2011). …”
mentioning
confidence: 99%
“…Stigma and prejudice can further prevent lesbian and gay care‐givers from accessing support from other sources, such as carer support groups (Barrett & Crameri, ; Brotman et al, ; Kia, ; Moore, ; Price, ). Older lesbian and gay people in particular can also struggle to find social support due to some lesbian and gay community groups being more youth‐oriented (Jacobs, Rasmussen, & Hohman, ; Kia, ; Lyons et al, ) and due to a lower likelihood of having a partner, children or contact with their families of origin (Croghan et al, ; Hash & Mankowski, ). A lower likelihood of having a partner and children may be partly due to the marginalisation faced by gay and lesbian people, which can leave some of them with fewer opportunities to form relationships and have children (Barrett et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Given that the care-giving role involves interacting with health professionals, older lesbian and gay care-givers can face fears around experiencing discrimination in these interactions, especially when caring for a same-sex partner Fredriksen-Goldsen & Muraco, 2010;Hash, 2006;Price, 2010;Washington et al, 2015;Willis, Ward, & Fish, 2011). For example, hospital staff may exclude from the decision-making process lesbian and gay care-givers who are a partner but not legally married to those they care for, or who are not biological family (Aronson, 1998;Coon, 2007;Fredriksen-Goldsen & Hooyman, 2007;Hash, 2001;Kia, 2012). Lesbian and gay care-givers have also reported that the expectation of stigma and discrimination about their sexual orientation affected how they dealt with health professionals in their care-giving role (Barrett, Whyte, Comfort, Lyons, & Crameri, 2015;Brotman et al, 2007;Hash, 2001;Price, 2010;Shippy, 2007;Washington et al, 2015).…”
mentioning
confidence: 99%
“…Importantly, within the scant body of research that reports on LGBTQ people's experiences with HBHC, it is noted that the margin of ‘freedom’ within LGBTQ homes and the potential for self‐expression and affirmation are indeed encroached upon by the hostility of some service providers, as reflected in LGBTQ people censuring displays of affection including touching, holding and kissing one another (Kia ). This paper aims to address the gap in the existing LGBTQ health services access literature by reporting qualitative pilot data on the LGBTQ education experiences and needs of HBHC providers working in one large, urban city in Ontario, Canada.…”
Section: Introductionmentioning
confidence: 99%